Six Values of Muhammad Nur Abdul Hafizh Suwaid's Moral Education for Early Childhood - Reno Andika; Rifdah Sabrina; Roni Pasaleron; Dafrizal Dafrizal; Hendra Syafrianto (Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur`an Sumatera Barat, 2023)
The application of the basic principles of Islamic teachings from the aqidah aspect of educating early childhood in the household can be applied based on the pillars that have been put forward by Muhammad Nur Abdul Hafizh Suwaid, namely dictating Tawheed sentences to children, instilling children's love for Allah, always asking for help and supervision. only to Allah and believe in the provisions of Allah SWT, instilling children's love for the Prophet Muhammad SAW, teaching the Qur’an to children, and instilling strong beliefs and a willingness to make sacrifices for it. The application of the basic principles of Islamic teachings from the aspect of worship educates young children in the household through from an early age parents have to get used to and teach children to pray, take children to the mosque, fast, teach about what the Hajj is, and zakat. The application of the basic principles of Islamic teachings from the moral aspect of educating young children in the household is based on Muhammad Suwaid's opinion, namely teaching children from an early age about manners, honesty, keeping secrets, being trustworthy, open-minded, and not being envious.